Volume 1: Turbomachinery 1995
DOI: 10.1115/95-gt-242
|View full text |Cite
|
Sign up to set email alerts
|

Performance Assessment of an Annular S-Shaped Duct

Abstract: An experimental investigation has been carried out to determine the aerodynamic performance of an annular S-shaped duct representative of that used to connect the compressor spools of aircraft gas turbine engines. For inlet conditions in which boundary layers are developed along an upstream entry length the static pressure, shear stress and velocity distributions are presented. The data shows that as a result of flow curvature significant streamwise pressure gradients exist within the duct, with this curvature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 0 publications
0
29
0
Order By: Relevance
“…As it was mentioned earlier, the value of the optimal slope increases with the parameters and so the duct becomes steeper. Optimal meridional duct length can be determined from (5), based on and corresponding OPT found from Figure 12(a). The lower value of parameter and the higher value of inlet swirl angle, the shorter duct length.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As it was mentioned earlier, the value of the optimal slope increases with the parameters and so the duct becomes steeper. Optimal meridional duct length can be determined from (5), based on and corresponding OPT found from Figure 12(a). The lower value of parameter and the higher value of inlet swirl angle, the shorter duct length.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Bailey et al [5] investigated the aerodynamic performance of a compressor s-shaped duct with a single strut. The data have shown that, as a result of flow curvature, significant streamwise pressure gradients exist within the duct, with this curvature also affecting the generation and suppression of turbulence.…”
Section: Introductionmentioning
confidence: 99%
“…As soon as flow approaches to the outer wall of the first bend, its pressure gets higher than the inner wall and consequently across the first bend, a pressure gradient is observed. However, this occurrence is altered within the second bend [3][4][5]. The S-shaped compressor transition duct is referred to as an S-shaped duct in the subsequent sections of the manuscript.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some studies have been reported on S-shaped ducts (Britchford et al, 1994;Bailey et al, 1995;Bailey and Carrotte, 1996). Their long-term objective is to apply CFD methods to enable the optimum design of S-shaped ducts.…”
Section: Introductionmentioning
confidence: 99%